Perfil eletroforético plasmático em emas (Rhea americana) de diferentes faixas etárias - Conrado, Alexandre de Carvalho (2005)
A significant growth of rhea breeding has been happening in the last years, but there is still a lack of information about this specie. Thus, this study had the objectives of determining rheas reference range of electrophoresis, to verify differences due to age. Some parameters were evaluated in 45 rheas, grouped into four categories: G1 (n=10), animals with 15 days of age; G2 (n=10), animals with 30 days of age; G3 (n=10), animals with 45 days of age and G4 (n=15), animals with 1 year of age. Were verified homogeneity in the electrophoresis parameters analyzed in the birds inside of each age group. Differences were verified among groups of age in PPT, albumin, globulins and relationship albumin/globulin values. Also difference among groups for the α1, α2, β and γ fractions. Comparison among studied parameters with other avian species observed in the literature demonstrated that most values are not similar and they may not be used as pattern to this specie.